Usage of Facebook among the Palestinian students in Malaysia in maintaining relationships / Abdelrahman N.A Musleh - N.A Musleh, Abdelrahman (2014)
This research was conducted to explore the relationship between the Facebook usage and the Palestinian students in Malaysia in maintaining their relationships. This research aimed at examining the use motives and satisfactions for Facebook, and analyzing the maintenance of Relationships as a factor of Facebook use. Research followed uses and gratifications theory to achieve the research purpose by reviewing the model studies and by analyzing the quantitative data about information of the Palestinian students who study in Malaysia. 278 students were asked to fill the questionnaires that conducted based on the research questions. Results showed that the main purpose for using Facebook among the Palestinian student is to contact their relatives. In addition, the results indicated that the Palestinian students are satisfied with the Facebook as a tool that let them to maintain their relationships with their relatives, and it is considered one of the highest motives that the Palestinian students use the Facebook for.